Instilling Universal Virtues Through Class Agreement In Early Childhood Character Development - Rahayu, Emy Puji Rahayu; Aisyah, Eny Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to instill universal virtues through class agreements in the context of developing the character of early childhood. The research method used is a qualitative approach with a case study design. Data was collected through observation, interviews and documentation at school during the implementation of the class agreement. Observations were carried out during learning and interviews with class teachers as well as documentation to support activities. The results of the research showed that involving children in preparing class agreements was an effective medium for instilling universal virtues, children's active participation in class agreements trained them to be responsible for themselves and surrounding environment, universal virtues can be practiced consistently through various daily activities at school, collaboration between teachers, children and parents creates continuity between character formation at school and at home. The results of this research showed that 80% of children understood virtue values, 87% of children were able to take responsibility for themselves and 97% of children were able to practice virtue values ​​in their activities. The implications of this research indicate that the class agreement approach can be an effective strategy in developing the character of early childhood. Continuous support from the school and parents is very important to ensure these universal virtues are embedded in children's lives holistically.